Branched PLGA derivatives with tailored drug delivery properties - Snejdrova Eva; Podzimek Stepan; Martiska Juraj; Holas Ondrej; Dittrich Milan (Acta Pharmaceutica)
Despite several shortcomings such as extreme hydrophobicity, low drug capacity, characteristic triphasic drug release pattern with a high burst effect, poly(lactic-co-glycolic acid derivatives are widely used in drug delivery. Most frequent attempts to improve their properties are blending with other polymers or synthesis of block copolymers. We introduce a new class of branched poly(lactic-co-glycolic acid) derivatives as promising biodegradable carriers for prolonged or targeted drug release systems, employed as thin adhesive films, solid dispersions, in situ forming implants or nanoparticles. A series of poly(lactic-co-glycolic acid) derivatives with lower molar mass and star or comb architecture were synthesized by a simple, catalyst free, direct melt polycondensation method not requiring purification of the obtained sterile product by precipitation. Branching monomers used were mannitol, pentaerythritol, dipentaerythritol, tripentaerythritol and polyacrylic acid. The products were characterized by molar mass averages, average branching ratio, rheological and thermal properties.